2022
DOI: 10.1055/s-0041-1741450
|View full text |Cite
|
Sign up to set email alerts
|

Adequacy of Antenatal Care during the COVID-19 Pandemic: Observational Study with Postpartum Women

Abstract: Objective The present study aimed to evaluate the antenatal care adequacy for women who gave birth at the University Hospital of Santa Catarina in Florianopolis (Brazil) during the COVID-19 pandemic, and to evaluate the association of adequacy with sociodemographic, clinical, and access characteristics. Methods Data were collected between October and December 2020, including 254 patients who delivered in the University Hospital from Federal University of Santa Catarina and answered our questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
(98 reference statements)
1
8
0
Order By: Relevance
“…Studies have reported efforts to align in-person visits with essential obstetric testing, yet the frequency with which such testing was completed during the height of the pandemic is rarely described ( 3 ). There are also reports of combining ultrasound-based tests (e.g., first trimester dating ultrasound with an ultrasound to measure nuchal translucency) and examining completion of third trimester testing for HIV, syphilis, and routine urine collection as a marker of the adequacy of prenatal care ( 2 , 9 ). Yet, despite the importance of second trimester testing in the ongoing management of a pregnancy and associated implications for the infant, from identification of birth defects to glucose monitoring after birth, the frequency and timing of such testing during the pandemic remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported efforts to align in-person visits with essential obstetric testing, yet the frequency with which such testing was completed during the height of the pandemic is rarely described ( 3 ). There are also reports of combining ultrasound-based tests (e.g., first trimester dating ultrasound with an ultrasound to measure nuchal translucency) and examining completion of third trimester testing for HIV, syphilis, and routine urine collection as a marker of the adequacy of prenatal care ( 2 , 9 ). Yet, despite the importance of second trimester testing in the ongoing management of a pregnancy and associated implications for the infant, from identification of birth defects to glucose monitoring after birth, the frequency and timing of such testing during the pandemic remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…We enthusiastically read the analysis conducted in the study Adequacy of Prenatal Care During The COVID-19 Pandemic: An Observational Study with Postpartum Women, 1 published in volume 44 issue #4 of the Brazilian Journal of Gynecology and Obstetrics in 2022, and would like to bring some considerations about the topic.…”
mentioning
confidence: 99%
“…3 4 However, the few current studies analyzing the quality of prenatal care in this region differ from the data made available by the Ministry of Health (MH). 1 5 Thus, it is pertinent to emphasize that this study has great value by making a careful analysis of this assistance.…”
mentioning
confidence: 99%
See 2 more Smart Citations